2012
DOI: 10.1118/1.4771932
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of beam angle selection strategies for intracranial IMRT

Abstract: Both BAS strategies incorporating FO by CO and independent BAS strategies excluding FO provide dose savings in OARs for optimized coplanar and especially noncoplanar beam ensembles; they should not be neglected in the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 58 publications
0
65
0
Order By: Relevance
“…45 For step&shoot IMRT, it has been established that such noncoplanar irradiation fields may allow for substantial dose reductions in OARs, especially if the OARs are close to irregularly shaped target volumes that are located asymmetrically within the body. [46][47][48][49] Leaving potential issues regarding patient immobilization on a robotic couch aside, the first treatment planning studies investigating noncoplanar VMAT have reconfirmed a benefit of noncoplanar irradiation with regard to OAR sparing. 33,45,47,[50][51][52][53] From the mathematical and technical side, the optimization of an irradiation trajectory shares the known issues of beam angle optimization (BAO) for step&shoot IMRT.…”
Section: E Noncoplanar Generalizations Of Vmatmentioning
confidence: 99%
See 1 more Smart Citation
“…45 For step&shoot IMRT, it has been established that such noncoplanar irradiation fields may allow for substantial dose reductions in OARs, especially if the OARs are close to irregularly shaped target volumes that are located asymmetrically within the body. [46][47][48][49] Leaving potential issues regarding patient immobilization on a robotic couch aside, the first treatment planning studies investigating noncoplanar VMAT have reconfirmed a benefit of noncoplanar irradiation with regard to OAR sparing. 33,45,47,[50][51][52][53] From the mathematical and technical side, the optimization of an irradiation trajectory shares the known issues of beam angle optimization (BAO) for step&shoot IMRT.…”
Section: E Noncoplanar Generalizations Of Vmatmentioning
confidence: 99%
“…The trajectories used for the above treatment planning studies were either found through inspection by a human planner, [50][51][52] using geometric heuristics, 45,53 or exhaustive search considering nine different couch tilts. 47 Wild et al 33 use a noncoplanar beam ensemble which was optimized with a genetic algorithm 49 for step&shoot IMRT to construct a noncoplanar VMAT trajectory. By connecting the optimized discrete beam orientations to a rotation trajectory, they could reproduce the dosimetric quality of the noncoplanar step&shoot IMRT treatment plan.…”
Section: E Noncoplanar Generalizations Of Vmatmentioning
confidence: 99%
“…Furthermore, for some types of cancers cases, e.g. intra-cranial tumors, the use of noncoplanar incidence directions improves substantially the treatment plan quality [5].…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of solving the BAO problem, a highly non-convex problem with many local minima on a large search space [14], is one possible justification for the manual selection or the use of coplanar incidence directions. However, evidence shows that noncoplanar incidence directions can lead to better treatment plans compared to plans obtained with coplanar incidence directions [5,33,38]. Moreover, the use of noncoplanar incidence directions is decisive for some types of cancers cases, e.g., brain tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that almost every angle is possible for radiation delivery, the use of coplanar angles, i.e., angles that lay in the plane of rotation of the gantry, is predominant. Furthermore, regardless of the evidence presented in the literature that selecting appropriate radiation beam incidence directions -beam angle optimization (BAO) problemcan lead to a plan's quality improvement [4,5,37], in clinical practice, most of the time, beam directions continue to be either manually selected by the treatment planner in a time-consuming trial and error iterative process or patients are irradiated using evenly spaced coplanar beams. The difficulty of solving the BAO problem, a highly non-convex problem with many local minima on a large search space [14], is one possible justification for the manual selection or the use of coplanar incidence directions.…”
Section: Introductionmentioning
confidence: 99%